Dividend policy from the perspective of an individual investor – results of the research - Jabłoński, Bartłomiej (Polityka dywidend z perspektywy postaw inwestora indywidualnego – wyniki badań, 2015)
The article describes the issues of dividend policy from the perspective of the psychology of the individual investor. A questionnaire survey conducted on 115 Polish stock exchange investors of different age, education, investment goals and professional activity aimed primarily at verifying the behaviour of the respondents in relation to the behaviour of the investors acting on the international market. The findings of the research not only confirm the convergence of the behaviour of Polish capital market investors against the behavioural dogmas of finance, but they also present new patterns of behaviour, provided that factors influencing an investment the decision-making process are taken into account
Nauki o Finansach = Financial Sciences, 2015, Nr 4 (25), s. 51-76
Keywords: behavioural finance; investment decisions; dividend policy; finanse behawioralne; decyzje inwestycyjne; polityka dywidend